2015
DOI: 10.4103/0253-7176.150809
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency: An Important Reversible Co-Morbidity in Neuropsychiatric Manifestations

Abstract: Background:Vitamin B12 deficiency is a common condition causing neurologic, cognitive, psychiatric, and mood symptoms. With varied religious, ethnic, and socioeconomic heterogeneity among the people in India greatly influencing their dietary habits and with the high prevalence of Helicobacter pylori infection, Vitamin B12 deficiency is not uncommon, but is often under recognized due to the lack of classical symptomatic presentation.Materials and Methods:Retrospective study on Vitamin B12 deficiency with neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…Falta evidencia que pueda apoyar esta hipótesis, pero algunos autores recomiendan hacer tamizaje en el primer episodio de manía, y con mayor indicación si no hay historia familiar de trastornos afectivos (63,64). Se han informado en algunos estudios niveles séricos bajos de vitamina B12, pero en otros no se ha encontrado diferencia o han sido altos (60)(61)(62).…”
Section: Psicosis Delirio Y Otros Trastornos Psiquiátricosunclassified
See 1 more Smart Citation
“…Falta evidencia que pueda apoyar esta hipótesis, pero algunos autores recomiendan hacer tamizaje en el primer episodio de manía, y con mayor indicación si no hay historia familiar de trastornos afectivos (63,64). Se han informado en algunos estudios niveles séricos bajos de vitamina B12, pero en otros no se ha encontrado diferencia o han sido altos (60)(61)(62).…”
Section: Psicosis Delirio Y Otros Trastornos Psiquiátricosunclassified
“…El diagnóstico de hipovitaminosis B12 por medición de los niveles séricos permite la siguiente clasificación: 1) "bajos" cuando son menores de 150-200 pg/ mL (75); 2) "normales" cuando están por encima de 350 pg/mL; en este último caso es improbable que los síntomas neuropsiquiátricos se expliquen por hipovitaminosis (9,35,63); 3) un rango llamado "normal bajo" entre 150-200 pg/mL y 350 pg/mL, en el que la mayoría de los estudios recomiendan medir el ácido metilmalónico para poder definir si existe o no una hipovitaminosis real (9,35,63,76). Ante las dificultades para medir dicho ácido, algunos autores recomiendan la reposición vitamínica cuando los niveles son inferiores a 350 pg/mL (2).…”
Section: Tamizaje Y Niveles Séricosunclassified
“…Previous studies have investigated the role of nutritional factors in treating neuropsychiatric disorders (9)(10)(11). These studies have shown that a considerable portion of patients with psychiatric disorders, including MDD, have been reported as having low levels of different vitamins, especially folate (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…concluded that Vitamin B12 deficiency, common in India, increases the load of cognitive decline and accentuates vascular risk factors in neuropsychiatric illnesses; it also increases homocysteine (Hcy) levels contributing to the vascular comorbidity in cerebro-and cardio-vascular disorders, thereby correcting this reversible Vitamin B12 deficiency state is of profound importance. [ 1 ]…”
mentioning
confidence: 99%
“…In this regard, Helicobacter pylori infection (Hp-I), also very common in India, is a potential environmental risk factor contributing to the pathophysiology of several neuropsychiatric diseases. Based on the histologic analysis of gastric mucosa biopsy for the documentation of Hp-I, a higher prevalence of Hp-I in Alzheimer's disease (AD) and mild cognitive impairment (MCI) patients in a Greek cohort has been found accompanied with increased Hcy concentration, an independent risk factor for dementia and AD,[ 2 3 4 ] also mentioned by the authors;[ 1 ] increased cerebrospinal fluid anti-Hp IgG antibody levels in AD patients may reflect the disease severity, and Hp eradication may positively influence AD manifestations at 2- and 5-year clinical endpoints. [ 2 3 4 ] Consistent associations with the Greek data were shown in subsequent studies from France, USA, and China, supporting Hp-I role in AD pathobiology.…”
mentioning
confidence: 99%